2018
DOI: 10.1111/mms.12488
|View full text |Cite
|
Sign up to set email alerts
|

Clicks of dwarf sperm whales (Kogia sima)

Abstract: The two species of the genus Kogia are widely distributed throughout the world's temperate and tropical oceans, but because they are small and highly cryptic, they are difficult to monitor. The acoustic signals of K. breviceps have been described previously, but the signals of K. sima have remained unknown. Here we present three recordings of K. sima, two from free-ranging animals and one from a captive setting, representing both the Atlantic Ocean and Pacific Ocean. The acoustic signals of K. sima are very si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…When modeling the propagation of echolocation clicks we used an average of 90-96 kHz since this best represents the bandwidth of the recorded click, but we compensated for the measured difference of 16 dB between the peak energy that would be available at 117 kHz and what was measured at 100 kHz. The characteristics of clicks from dwarf sperm whales recorded in the wild near The Bahamas and Guam (Merkens et al, 2018), and a captive pygmy sperm whale that stranded from the Western Atlantic (Madsen et al, 2005), are reported in Table 1. The peak frequencies in the MC recordings are slightly lower (117 kHz), and the pulse durations are shorter (62 µs) than in the reported Kogia recordings.…”
Section: Kogia Spp Acousticsmentioning
confidence: 99%
See 1 more Smart Citation
“…When modeling the propagation of echolocation clicks we used an average of 90-96 kHz since this best represents the bandwidth of the recorded click, but we compensated for the measured difference of 16 dB between the peak energy that would be available at 117 kHz and what was measured at 100 kHz. The characteristics of clicks from dwarf sperm whales recorded in the wild near The Bahamas and Guam (Merkens et al, 2018), and a captive pygmy sperm whale that stranded from the Western Atlantic (Madsen et al, 2005), are reported in Table 1. The peak frequencies in the MC recordings are slightly lower (117 kHz), and the pulse durations are shorter (62 µs) than in the reported Kogia recordings.…”
Section: Kogia Spp Acousticsmentioning
confidence: 99%
“…On two occasions, pygmy sperm whales in captivity have been shown to produce high-frequency, narrow-band clicks with peak frequencies around 125-130 kHz (Marten, 2000;Ridgway and Carder, 2001;Madsen et al, 2005). Based on field recordings, dwarf sperm whales are known to produce similarly high-frequency clicks (Merkens et al, 2018). The highfrequency echolocation signals of pygmy and dwarf sperm whales are similar to those of phocoenids, cephalorhynchids and two lagenorhynchid species (Au, 1993;Bassett et al, 2009;Kyhn et al, 2009Kyhn et al, , 2010; however, none of the latter species are known to occur in the GOM (Wursig et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…K. sima also produce similar high‐frequency, narrow‐band clicks (Merkens et al . ). The HARPs were unable to capture the full frequency range of the clicks of these species, but the portion of the click energy below 100 kHz was recorded and some energy above 100 kHz may have been aliased down and thus recorded as well (Fig.…”
Section: Shipboard and Aerial Visual Survey Effort For Each Locationmentioning
confidence: 97%
“…Two species of Kogia are found in BC and believed to forage for cephalopods in mid-to deep-waters 106 . All four species differ in mean characteristics of their clicks, but have considerable overlap in acoustic bandwidth [107][108][109] . The difficulty in acoustic species identification for porpoises and Kogia due to high variability of presumed Kogia clicks has been recently demonstrated 110 , therefore further work is required to distinguish these species acoustically.…”
Section: Speciesmentioning
confidence: 99%